Workplace presenteeism, job substitutability and gender inequality - Ghazala Azmat; Lena Hensvik; Olof Rosenqvist (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2020)
Following the arrival of the first child, women's absence rates soar and become less predictable due to the greater frequency of their own sickness and the need to care for sick children. In this paper, we argue that this fall in presenteeism in the workplace hurts women's wages, not only indirectly and gradually, through a slower accumulation of human capital, but also immediately, through a direct negative effect on productivity in unique jobs (i.e., jobs with low substitutability). Although both presenteeism and uniqueness are highly rewarded, we document that women's likelihood of holding jobs with low substitutability decreases substantially relative to men's after the arrival of the first child. This gap persists over time, with important long-run wage implications. We highlight that the parenthood wage penalty for women could be reduced by organizing work in such a way that more employees have tasks that, at least in the short run, can be performed satisfactorily by other employees in the workplace.
Keywords: J16; J22; 330; first child; presenteeism; couples; job substitutability; gender wage gap